2022
DOI: 10.3389/fpsyt.2022.933848
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged grief disorder in Arabic-speaking treatment-seeking populations: Relationship with socio-demographic aspects, loss- and trauma-related characteristics, and mental health support

Abstract: Prolonged grief disorder in Arabic-speaking treatment-seeking populations: Relationship with socio-demographic aspects, loss-and trauma-related characteristics, and mental health support. Front. Psychiatry : . doi: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Studies found several demographic factors that increase the risk for development of PGD, such as lower socioeconomic status, being female, and being older (Gilbar and Ben-Zur, 2002 ; Ferrario et al, 2004 ; Simon et al, 2005 ; Vanderwerker et al, 2006 ; Kersting et al, 2011 ; Newson et al, 2011 ; Sung et al, 2011 ; Hu et al, 2015 ; Fernández-Alcántara and Zech, 2017 ; Heeke et al, 2017 ; Lundorff et al, 2017 ; Specht et al, 2022 ). As these factors vary across cultural contexts and are related to cultural diversity, such as race, common mental health problems, socioeconomic constructs, and cultural norms and beliefs, they might affect the experience of losing a loved one and consequently the likelihood of developing PGD.…”
Section: Risk Factors For Prolonged Grief Disorder In the Global Contextmentioning
confidence: 99%
“…Studies found several demographic factors that increase the risk for development of PGD, such as lower socioeconomic status, being female, and being older (Gilbar and Ben-Zur, 2002 ; Ferrario et al, 2004 ; Simon et al, 2005 ; Vanderwerker et al, 2006 ; Kersting et al, 2011 ; Newson et al, 2011 ; Sung et al, 2011 ; Hu et al, 2015 ; Fernández-Alcántara and Zech, 2017 ; Heeke et al, 2017 ; Lundorff et al, 2017 ; Specht et al, 2022 ). As these factors vary across cultural contexts and are related to cultural diversity, such as race, common mental health problems, socioeconomic constructs, and cultural norms and beliefs, they might affect the experience of losing a loved one and consequently the likelihood of developing PGD.…”
Section: Risk Factors For Prolonged Grief Disorder In the Global Contextmentioning
confidence: 99%